Emerging threats to equitable implementation of ART in South Africa - Stewart, Robert; Padarath, Ashnie; Milford, Cecilia (University of the Free State, 2006)
The Comprehensive Plan for the expanded treatment of HIV in South Africa was lodged in November 2003. The guiding principles of this plan are “universal access to care and treatment for all, irrespective of race, colour, gender and economic status”, and equitable implementation. However, there are concerns that the provision of antiretroviral treatment will exacerbate existing inequities, thereby undermining the very system that it seeks to build. Using a monitoring framework developed by EQUINET, this contribution seeks to identify the shortfalls in programme implementation and threats to achieving the equity goals that are emerging. Findings highlight ongoing concerns around weak monitoring systems and data collection that enable the development of equity profiles at a sub-national level, while limiting the extent to which progress in meeting the guiding principles may be assessed.

Die Komprehensiewe Plan vir die uitgebreide behandeling van MIV is in November 2003 in Suid-Afrika bekendgestel. Die rigtinggewende beginsels van hierdie plan is universele toegang tot sorg en behandeling vir almal, ongeag ras, kleur, geslag en ekonomiese status, en die regverdige implementering daarvan. Nogtans is daar kommer dat die voorsiening van antiretrovirale behandeling bestaande ongelykhede sal vererger en daardeur juis die sisteem wat dit probeer bou, sal ondermyn. Deur die aanwending van ’n moniteringsraamwerk wat deur EQUINET ontwikkel is, wil hierdie bydrae tekortkominge in programimplementering en ontwikkelende bedreigings vir die verwesenliking van billikheidsdoelstellings identifiseer. Bevindinge werp lig op voortgesette vrese oor swak moniteringsisteme en dataversameling om die daarstelling van billikheidsprofiele op ’n sub-nasionale vlak moontlik te maak. Dit werk beperkend in op die mate waarin vordering met voldoening aan die riglyne gemeet kan word.
Keywords: HIV and AIDS; Treatment; South Africa; Antiretroviral treatment (ART)